2010
DOI: 10.1063/1.3446832
|View full text |Cite
|
Sign up to set email alerts
|

Extreme water state produced by underwater wire-array electrical explosion

Abstract: The generation of an extreme water state ͑130 GPa, 5000 K, and 3.4 g / cm 3 ͒ which is characterized as dense plasma at the axis of a converging shock wave is reported. A 4 kJ pulse generator was used to explode a 40 Cu-wire array, generating a cylindrical shock wave. The measured shock wave trajectory and energy deposited into the water flow were used in hydrodynamic simulations coupled with the equation of state to determine the water parameters. The temperature estimated using the emission data of water in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…A detailed overview of the exploding wire technique and its application in shock-wave generation can be found elsewhere (Fedotov-Gefen et al. 2010; Liverts et al. 2015; Sembian et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed overview of the exploding wire technique and its application in shock-wave generation can be found elsewhere (Fedotov-Gefen et al. 2010; Liverts et al. 2015; Sembian et al.…”
Section: Methodsmentioning
confidence: 99%
“…air at 1 atm and 298 K in the present case. A detailed overview of the exploding wire technique and its application in shock-wave generation can be found elsewhere (Fedotov-Gefen et al 2010;Liverts et al 2015;Sembian et al 2016b;Sharma et al 2021c). In comparison with diaphragm-based conventional shock tubes, the present technique provides several advantages such as a small-size test facility, ease of operation, extensive range of shock Mach numbers (M s = 1 to 6; Sembian et al 2016b) and high repeatability between the tests.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…Researchers from Israel Institute of Technology verified the metal equation of state (EOS) and conductivity model based on nanosecond and microsecond time-scale UEWE [41][42][43]. Cylindrical and spherical wire arrays were used to generate convergent underwater shock waves (SWs) with pressure as high as 6.6 TPa and water compression ratio ∼9 [44]; a large amount of research on SW converging process and water state at extreme pressure [45][46][47][48][49][50][51][52] has been carried out in Israel Institute of Technology, Imperial College London, Tsinghua University, etc. Taking advantage of the high energy deposition, UEWE is used to synthesize metal nanoparticles with smaller diameter and narrower size distribution than the gas medium EWE [53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…The results of recent research Grinenko et al, 2007;Fedotov et al, 2007;Fedotov-Gefen et al, 2010 on underwater electrical wire array explosions showed that this method can be considered as an alternative to that using light gas guns (Mitchell & Nellis, 1981), Z-pinch (Spielman et al, 1998), powerful lasers (Celliers et al, 2004;Kolacek et al, 2010), or intense heavy ion beams (Tahir et al, 2010) to form warm dense matter (Sasaki et al, 2006). In addition, this method can be especially useful for studying water in extreme states, which is important for studying the physics of giant planets (Lindl et al, 1995;Nellis et al, 1997;Goldman et al, 2009).…”
Section: Introductionmentioning
confidence: 99%